Successful Treatment of Mepolizumab- and Prednisolone-resistant Allergic Bronchopulmonary Aspergillosis with Dupilumab - Mikura, Sunao; Saraya, Takeshi; Yoshida, Yuki; Oda, Miku; Ishida, Manabu; Honda, Kojiro; Nakamoto, Keitaro; Tamura, Masaki; Takata, Saori; Shimoyamada, Hiroaki; Fujiwara, Masachika; Ishii, Haruyuki (Internal Medicine, 2021)
A 45-year-old man with allergic bronchopulmonary aspergillosis (ABPA) was treated with oral prednisolone (PSL) (30 mg/day), inhaled corticosteroids, and long-acting beta2-agonists. After confirmation of a PSL-dependent status (8 mg/day), subcutaneous injection with anti-interleukin (IL)-5 antibody (mepolizumab, 100 mg/month) was performed, and the PSL dose was tapered to 5 mg/day. However, ABPA recurred and proved refractory to oral itraconazole (200 mg/day). Alternative subcutaneous injection therapy with dupilumab (induction dose of 600 mg followed by a maintenance dose of 300 mg/2 weeks) enabled the successful withdrawal of oral PSL without clinical deterioration. This case demonstrates the potential utility of dupilumab for steroid-dependent ABPA via the synergistic suppression of IL-4 and IL-13 compared to monotherapy with anti-IL-5 antibody.